Effect of comorbidities and risk conditions on death from COVID-19 in migrants in Mexico - Oscar A. Martínez-Martínez; Karla A. Valenzuela-Moreno; Brenda Coutiño (BMC, 2021)
Abstract Background Comorbidities increase the risk of death for patients with COVID-19, however, little is known about how it affects the prognosis of migrants who contract the virus. Therefore, this article aims to determine which comorbidities and risk conditions are associated with the probability of death among migrants infected with COVID-19 in Mexico. Methods We use a sample of migrants with a positive diagnosis for COVID-19 (N = 2126) registered in the public database published in the National Epidemiological Surveillance System of the Mexican Ministry of Health; the technique used was a Probit regression. Results The findings show that most of the comorbidities commonly associated with death from COVID-19 in the native-born population were actually not significant when present in migrants infected with COVID-19. Additionally, migrants have lower comorbidities than locals. The results further indicate that the factors related to the death of migrants infected with COVID-19 are: age, intubation, nationality group, pneumonia and the Health Care Management of Patients. Conclusions In contrast to preceding studies with native-born populations with COVID-19, where pre-existing diseases aggravated the diagnosis of COVID-19 and sometimes led to death, in the case of migrants, only pneumonia was the significant comorbidity associated with mortality among migrants diagnosed with COVID-19.